2018
DOI: 10.1186/s12889-018-5436-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of child and adolescent psychiatric disorders in Lithuania

Abstract: BackgroundFrom the public health perspective, epidemiological data of child mental health and psychosocial correlates were necessary and very lacking in Lithuanian society that has been undergoing rapid socio-economic change since the past decades. Together with determining the prevalence rates of disorders and assessing the needs for the services, this study has also shifted attention from the highly selective samples of children attending children and adolescent mental health services towards less severe cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 38 publications
4
44
1
4
Order By: Relevance
“…11 The finding of the Kenyan study is also consistent with our finding. Contrary to the current study, the lower prevalence of EBP was reported in Lithuania (14.05%) 8 and Nepal (12.9%-17.03%). 9 The difference might be due to different countries' socioeconomic status, the age of children involved in the study (7-10 years) and year of study such as study conducted in Lithuania (2004)(2005)(2006)(2007).…”
Section: General Psychiatrycontrasting
confidence: 99%
See 1 more Smart Citation
“…11 The finding of the Kenyan study is also consistent with our finding. Contrary to the current study, the lower prevalence of EBP was reported in Lithuania (14.05%) 8 and Nepal (12.9%-17.03%). 9 The difference might be due to different countries' socioeconomic status, the age of children involved in the study (7-10 years) and year of study such as study conducted in Lithuania (2004)(2005)(2006)(2007).…”
Section: General Psychiatrycontrasting
confidence: 99%
“…In this study, higher prevalence of conduct (7.1%) and anxiety disorders (5.9%) than ADHD (2.9%), was reported. 8 In Nepal, the prevalence of EBPs in school children was 12.9%-17.03%. The clinical prevalence of anxiety disorders was 18.8%-24.4% and ADHD was 10%-11.7% in different clinical samples of children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no epidemiological studies on the prevalence of eating disorders or disordered eating were performed in Lithuania. However, body image concerns, health‐compromising eating behaviors, disordered eating, and the prevalence of psychosomatic and psychiatric disorders constitute a significant problem and area of research in young people globally and in Lithuania (Baceviciene, Jankauskiene, & Emeljanovas, ; Jankauskiene & Baceviciene, ; Lesinskiene et al, ). The reduction in EDs and health‐compromising eating behaviors is one of the most important targets in prevention programs for obesity and body image concerns (Ciao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The region of Northern Europe has a minor but significant increasing trend in adolescent PHC between 1980 and 2016 [13]. However, PHC in adolescents has not attracted much scientific attention in Lithuania, despite the relatively high overall prevalence of youth psychiatric disorders compared with Western European countries [14]. Therefore, the analysis of the factors associated with Lithuanian adolescents’ psychosocial well-being and lifestyle factors is very important [15].…”
Section: Introductionmentioning
confidence: 99%